The INAF-Arcetri Astrophysical Observatory contribution to SKA-Low: technology and first observations - Macario, Giulia; Baffa, Carlo; Belli, Carolina; Bolli, Pietro; Chiarucci, Simone; Comoretto, Giovanni; Di Ninni, Paola; Giani, Elisabetta; Kyriakou, Georgios (Il Colle di Galileo, 2022)
SKA (Square Kilometre Array), the largest and most powerful interferometric array of radio telescopes in the world in the 50 MHz to 15 GHz frequency range is currently under construction. Its unprecedented performance will revolutionize modern astrophysics starting from the next decade. The technological radioastronomical group at the INAF-Arcetri Astrophysical Observatory is actively involved in the design, development and validation of SKA-Low, the low-frequency (50-350 MHz) component of SKA.